2020
DOI: 10.19168/jyasar.716064
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Food Quality, Satisfaction, Brand Image In Restaurants And Recommendation Intention Relation

Abstract: In this study, the interaction in between recommendation intention and perceived food quality, satisfaction, brand image is examined. The relations among stated variables are statistically analysed with structural equation modelling. Conceptual framework is formed by having literature review and a questionnaire is applied to 361 consumers dined at Köfteci R. restaurant located in İzmir, with convenience sampling method. In the study, descriptive (percentage, average, standard deviation) and predictive statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
1
7
0
2
Order By: Relevance
“…The findings of both studies supported H3. In addition to the very few studies on perceived quality and recommendation intention (Taube and Heinberg, 2011; Solunoğlu, 2020), the current study showed that servitization is effective on recommendation intentions through the mediating role of perceived quality. This result filled a gap in the literature and pointed out that integrating services in a retail fashion brand's marketing offering contributes to quality perceptions and recommendation intentions.…”
Section: Theoretical Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The findings of both studies supported H3. In addition to the very few studies on perceived quality and recommendation intention (Taube and Heinberg, 2011; Solunoğlu, 2020), the current study showed that servitization is effective on recommendation intentions through the mediating role of perceived quality. This result filled a gap in the literature and pointed out that integrating services in a retail fashion brand's marketing offering contributes to quality perceptions and recommendation intentions.…”
Section: Theoretical Discussionsupporting
confidence: 59%
“…In addition to purchase intentions, perceived quality has a positive influence on recommendation intentions. Perceived food quality leads to higher recommendation intentions (Solunoğlu, 2020). For Fast-moving Consumer Goods products, Taube and Heinberg (2011) found that perceived quality significantly impacts recommendation intentions.…”
Section: Purchase and Recommendation Intentionsmentioning
confidence: 99%
“…Similarly, Back et al (2021), Haji et al (2021), Amin et al (2021), Çevik and Şimşek (2020), Gohary et al (2020), Solunoğlu (2020), Tavitiyaman and Qu (2013) and Belanche et al (2012) concluded that satisfaction positively affects the behavioral intention and other intentions. Satisfied tourists provide many advantages to the hotel establishments that use the halal concept.…”
Section: Discussionmentioning
confidence: 94%
“…Food Quality didefinisikan sebagai sesuatu yang ditawarkan dan dijual produsen makanan kepada konsumennya supaya dibeli lalu digunakan dalam rangka memenuhi kebutuhan-kebutuhan konsumen (Slack et al, 2021). Menurut Solunoglu (2020), food quality merupakan elemen krusial dalam sektor makanan, yang memiliki atribut yang dijadikan faktor utama dalam upaya mencapai standar kualitas makanan yang sesuai. Ini meliputi aspek-aspek seperti tampilan visual, rasa, kekonsistenan, tekstur, dimensi, dan warna.…”
Section: Food Qualityunclassified